2019
DOI: 10.3390/molecules24173126
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antioxidative Potential of the Blue Congo Variety of Purple Potato Extract in Streptozotocin-Induced Diabetic Rats

Abstract: This study was designed to evaluate the effects of purple potato extract of the Blue Congo variety (PP) on diabetes and its antioxidant activities after two-week administration tostreptozotocin (STZ)-induced diabetic rats. The activities of PP were evaluated at a dose of 165 mg/kg body weight (b.w.) by estimating biochemical changes in blood plasma and through a histopathological study of kidney, muscles, and liver tissue. We evaluated the effect of treatment with extract on glucose level, glycated hemoglobin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 60 publications
1
31
0
7
Order By: Relevance
“…Intraperitoneal injection of STZ had a necrotic effect on insulin-producing pancreatic β-cells leading to hyperglycemia and a significant decrease in insulin secretion within 48 h after injection. 53 In our study, there was a significant elevation in blood glucose in the study group compared to the control group. The same thing happened in the study group before and after injection of STZ in accordance with El-Baz et al, 54 who found that animals injected with STZ exhibited a significant elevation in glucose blood levels after 30 days by 2.7-folds, when compared to normal animals.…”
Section: Discussionsupporting
confidence: 44%
“…Intraperitoneal injection of STZ had a necrotic effect on insulin-producing pancreatic β-cells leading to hyperglycemia and a significant decrease in insulin secretion within 48 h after injection. 53 In our study, there was a significant elevation in blood glucose in the study group compared to the control group. The same thing happened in the study group before and after injection of STZ in accordance with El-Baz et al, 54 who found that animals injected with STZ exhibited a significant elevation in glucose blood levels after 30 days by 2.7-folds, when compared to normal animals.…”
Section: Discussionsupporting
confidence: 44%
“…BioMed Research International 7 histopathological study. Several investigations showed that STZ enters the pancreatic β-cells by glucose protein-2 transporter and disrupts the balance between antioxidant and oxidant systems damaging the insulin-producing islet β-cells and inducing the progression of diabetes [23,24]. Another study showed STZ produced islet β-cells injury, which in turn elevated glucose level and decreased insulin level [25].…”
Section: Discussionmentioning
confidence: 99%
“…The degradation product of LPO, malondialdehyde (MDA), reacts with TBA at 100° C to form colored complex. The level of MDA was expressed as nmol/mL of plasma or as pmol/million of leukocytes using 156,000 M −1 cm −1 as a molar absorption coefficient at λ = 532 nm [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The level of OMPs was determined following the method described by Demkovych et al [ 22 ] with a slight modification [ 20 ]. The method is based on spectrophotometric detection of hydrazones formed in the reaction of aldehyde and ketone groups of aliphatic amino acid residues with the 2,4-dinitrophenylhydrazine that absorb at λ = 370 nm (OMP 370 nm —OMPs of neutral characteristics) and at λ = 430 nm (OMP 430 nm —OMPs of basic characteristics).…”
Section: Methodsmentioning
confidence: 99%